Origin and hydrodynamics of xylem sap in tree stems, and relationship to root uptake of soil water - Yasunori Mahara (Nature Portfolio, 2021)
Abstract Although 10 years have passed since Japan’s Fukushima nuclear accident, the future radiation risk from 137Cs contamination of wood via root uptake is a serious concern. We estimated the depth at which the roots of evergreen coniferous sugi (Cryptomeria japonica) and broadleaf deciduous konara (Quercus serrata) trees actively take up soil water by using positive δD values from the artificial D2O tracer and seasonal changes in the δ18O values of soil water as a natural environmental tracer. We compared the tracer concentration changes in xylem sap with those in the soil water and ascertained that both tree species primarily took up water from a depth of 20 cm, though with mixing of water from other depths. Using sap hydrodynamics in tree stems, we found that water circulation was significantly slower in heartwood than in sapwood. Heartwood water was not supplied by direct root uptake of soil water. The measured diffusion coefficients for D2O, K+, Cs+, and I− in xylem stems were greater in sapwood than in heartwood, and their magnitude was inversely correlated with their molecular weights. The distribution of D2O and 137Cs concentrations along the radial stem could be explained by simulations using the simple advective diffusion model.